Species Richness and Stand Lliversity in Relation to Site and Succession of Forests in Sarawak and Brunei (Borneo) - Brünig, E. F. (Amazoniana, 1973)
Site conditions in the Mixed Dipterocarp forests of Sarawak and Brunei are characterised by the absence of prolonged drought. This permits minor site differences to become ecologically fdly effective. In the ker'ángas forests, drought conditions occur frequently and regularly. An extremely variable water regime and uniforrnity of chemical and physical soil conditíons are typical of kerangas peat bogs and deltaic peatswamp forest sites. Consequently, fewer niches are available and the number of species is less on these sites than in Mixed Dipterocarp forest. Upland kerangas sites are intermediate in this respect. About 850 tree species (428 genera) are recorded from kerangas forests. It is estimated that the total number of tree species in ali forest types in Sarawak and Brunei is between 2 500 and 3 000, and 2 800 and 3 300 respectively.
Keywords: Regime Hidrológico